2018
DOI: 10.1186/s12889-018-6002-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of risk factors and gaps in prevention strategies for mother-to-child HIV transmission in Rio de Janeiro, Brazil

Abstract: BackgroundDespite great progress made in methods to prevent mother-to-child transmission of HIV (MTCT), delivery and uptake of these measures remains a challenge in many countries. Although the Brazilian Ministry of Health aimed to eliminate MTCT by 2015, infection still occured in 15–24% of infants born to HIV-infected mothers. We sought to identify remaining factors that constrain MTCT elimination.MethodsWe conducted a retrospective, matched case-control study by reviewing hospital charts of infants born to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 18 publications
3
18
0
2
Order By: Relevance
“…Similar results were identified in a study of HIV-infected pregnant women from Rio de Janeiro between 1997 and 2014, in which 11.5% (50/435) did not receive an HIV diagnosis until after delivery. Additionally, while this study found an increase in prenatal HIV diagnosis across the study period, just 83% of mothers were diagnosed before or during the prenatal period in 2014 40.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Similar results were identified in a study of HIV-infected pregnant women from Rio de Janeiro between 1997 and 2014, in which 11.5% (50/435) did not receive an HIV diagnosis until after delivery. Additionally, while this study found an increase in prenatal HIV diagnosis across the study period, just 83% of mothers were diagnosed before or during the prenatal period in 2014 40.…”
Section: Resultsmentioning
confidence: 54%
“…A study of 1364 HIV-infected pregnant women between 2000 and 2009 across the northeast state of Ceará found an increase in prenatal attendance over the study period, although just 84.5% of women had attended any prenatal care in the final study year 37. In the Rio de Janeiro cohort of HIV-infected pregnant women from 1997 to 2014, prenatal care attendance increased over the study period, although again just 83.3% of HIV-infected pregnant women had at least one prenatal visit in 2014 40.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations